2015
DOI: 10.1097/md.0000000000001448
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 and 2 Common Genetic Variants and Risk for Restless Legs Syndrome

Abstract: Several neurochemical, neuropathological, neuroimaging, and experimental data, suggest that iron deficiency plays an important role in the pathophysiology of restless legs syndrome (RLS). Heme-oxygenases (HMOX) are an important defensive mechanism against oxidative stress, mainly through the degradation of heme to biliverdin, free iron, and carbon monoxide. We analyzed whether HMOX1 and HMOX2 genes are related with the risk to develop RLS.We analyzed the distribution of genotypes and allelic frequencies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 36 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…Since iron deficiency plays an important role in the pathogenesis of RLS, it is plausible that alteration in HMOX1 and HMOX2 gene could be related with RLS. This hypothesis is on the line of a previous study that suggested a weak association between HMOX1 polymorphism and the risk to develop RLS in the Spanish population [13].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Since iron deficiency plays an important role in the pathogenesis of RLS, it is plausible that alteration in HMOX1 and HMOX2 gene could be related with RLS. This hypothesis is on the line of a previous study that suggested a weak association between HMOX1 polymorphism and the risk to develop RLS in the Spanish population [13].…”
Section: Discussionsupporting
confidence: 75%
“…Garcia-Martin et al [13] selected 4 single nucleotide polymorphisms (SNPs) in HMOX1 and HMOX2, and only HMOX1 rs2071746 turned out to be associated with the risk for RLS in the Spanish population. The fact that HMOX2 rs4786504C allele contributes to a more efficient breakdown of heme and that HMOX2 rs1051308 is associated with the risk of developing Parkinson's disease (PD) also make us wonder if HMOX2 could be a risk factor for Chinese RLS [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study by our group, the frequencies of HMOX2 rs1051308A were higher in male patients with multiple sclerosis than in controls . This aside, a lack of a major association of this SNP with Parkinson's disease , restless legs syndrome and with age‐related macular degeneration has been reported.…”
Section: Discussionmentioning
confidence: 81%
“…We have previously reported association between HMOX1 rs2071746 variant and the risk for PD, ET, and restless legs syndrome 4 5 7 suggesting a possible link between these diseases. However, there are no clues on putative biological mechanisms underlying the association found.…”
Section: Discussionmentioning
confidence: 90%
“…Heme oxygenase occurs as 2 main isozymes, an inducible heme oxygenase-1 (HMOX1), and a constitutive heme oxygenase-2 (HMOX2), which are encoded by the genes designated, respectively, as HMOX1, HO-1 or HSP32 (gene identity 3162, chromosome 22q13.1) and HMOX2 or HO-2 (gene identity 3163, chromosome 16p13.3). Several recent studies have shown association between certain single nucleotide polymorphisms (SNPs) in the HMOX1 2 3 4 5 and HMOX2 4 6 genes and the risk for Parkinson’s disease (PD) 2 4 6 , essential tremor (ET) 5 , and restless legs syndrome 7 .…”
mentioning
confidence: 99%